SINGKRONISASI PERATURAN WALI KOTA TENTANG SANKSI ADMINISTRASI PELANGGARAN KETENTRAMAN DAN KETERTIBAN UMUM DI KOTA YOGYAKARTA - Hidayatulloh, Bagus Anwar (Jurnal Pengabdian Indonesia (JPI), 2025)
The legal outreach activity themed "Synchronization of the Mayor Regulation on Administrative Sanctions for Violations of Public Order and Peace in Yogyakarta City" aimed to enhance legal understanding and implementation capacity of the municipal police (Satpol PP). The discussions and interactive sessions highlighted the urgent need to harmonize and update the substance of the current regulation to align with good governance principles and ensure clear and proportional enforcement. Key challenges identified included weak regulatory structure, lack of technical guidelines, and limited objection mechanisms for affected citizens. The activity also produced normative recommendations in the form of a draft regulatory formulation, covering violation classification, types of administrative sanctions, sanction procedures, and appeal mechanisms. This outreach underlines the importance of a collaborative approach between academics and practitioners in formulating effective and just local legal policies.